Repragmatization of the ME TOO Speech Act in Social and Communicative Practices of the Internet - T. M. Shkapenko; N. B. Milyavskaya (Научный диалог)
The pragmatic nature of the Me too speech act is studied in two different areas of functioning: outside the Internet environment and in cyberspace. It is noted that in normal communication Me too is a response cue that closes an adjacency pair and does not have a persuasive potential. On the Internet, this speech act undergoes radical changes, turning into a stimulus statement that initiates the mass participation of a certain target audience in the movement against sexual harassment. It is shown that the pragmatic transformation of the phrase is due to the action of both linguistic and extralinguistic factors. The transition from a responsive cue to an initial utterance is ensured by a common presupposition for all addressees, while the versatility of intentions acquired by the speech act (affirmation, recognition, accusation, appeal) together with the deictic pronoun of the first person endow it with a high degree of persuasiveness. As the psychological basis for the effective impact of the phrase, the ideas of the American psychological school about the importance of empathy and the therapeutic effect of public actions - confessions are successfully introduced into the consciousness of a globalized community. The novelty of the study is that for the first time the fact of the limited relevance of individual postulates of pragmalinguistic theories for the Internet space is established. The relevance of the work is associated with the need for a comprehensive understanding of the phenomenon of repragmatization of the Me too , which receives the role of a semiotic marker and a cultural symbol of a new wave of the feminist movement.